Use of coronary CT angiography in the diagnosis of patients with suspected coronary artery disease: findings and clinical indications - Sun, Zhonghua; Liu, Y.; Zhou, D.; Qi, Y. (Chinese P L A General Hospital * Institute of Geriatric Cardiology, 2012)
Objective: To investigate the clinical applications of coronary CT angiography in patients with suspected coronary artery disease and identify factors that affect CT findings. Methods: Medical records of patients suspected of coronary artery disease over a period of 12 months from a tertiary teaching hospital were retrospectively reviewed. Patient age, sex (male/female), duration of symptoms and abnormal rates of coronary CT angiography scans were analysed to investigate the relationship among these parameters. The patients by age were characterized into five groups: under 36 years, 36–45 years, 46–55 years, 56–65 years and more than 66 years, respectively; while the duration of symptoms was also classified into five groups: less than one week, one week to one month, one to three months, three to six months and more than six months. Results: Of the 880 patient records reviewed, 800 met the above study criteria. Five hundred and forty nine patients demonstrated abnormal CT findings (68.6%). There was no significant difference in the percentage of abnormal CT findings based on patient sex and the duration of symptoms (P = 0.14). The abnormal rates of coronary CT angiography, however, increased significantly with increasing age (P < 0.001); with patients over 65 years of age 2.5 times more likely to have an abnormal CT scan relative to a patient under 45 years. A significant difference was found between abnormal coronary CT angiography and the duration of symptoms (P = 0.012). Conclusions: Our results indicate coronary CT angiography findings are significantly related to the patient age group and duration of symptoms. Clinical referral for coronary CT angiography of patients with suspected coronary artery disease needs to be justified with regard to the judicious use of this imaging modality.